2010
DOI: 10.1111/j.1365-2710.2009.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pentoxifylline on coagulation profile and disseminated intravascular coagulation incidence in Egyptian septic neonates

Abstract: Pentoxifylline protects against sepsis-induced microcirculatory derangement in neonates. It significantly lowered the incidence of bleeding and MODS and shortened the length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…PTX therapy in conjunction with antibiotics did not decrease the development of NEC. 14,[19][20][21][22][23][24] An interesting finding in our study is that the length of hospital stay, duration of antibiotics therapy and duration of respiratory support were significantly lower in preterm infants who received PTX. The latest Cochrane review has demonstrated that there is no reduction in the development of NEC in neonates with sepsis who had PTX as an adjunct to antibiotics compared with neonates with sepsis who had placebo [typical relative risk: 0.29 (95% CI: 0.07-1.24); typical RD: −0.20 (95% CI: −0.41 to 0.01)], and they also clarified that no completed randomized or quasi-randomized trials using PTX for the treatment of stage II or III NEC were identified.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…PTX therapy in conjunction with antibiotics did not decrease the development of NEC. 14,[19][20][21][22][23][24] An interesting finding in our study is that the length of hospital stay, duration of antibiotics therapy and duration of respiratory support were significantly lower in preterm infants who received PTX. The latest Cochrane review has demonstrated that there is no reduction in the development of NEC in neonates with sepsis who had PTX as an adjunct to antibiotics compared with neonates with sepsis who had placebo [typical relative risk: 0.29 (95% CI: 0.07-1.24); typical RD: −0.20 (95% CI: −0.41 to 0.01)], and they also clarified that no completed randomized or quasi-randomized trials using PTX for the treatment of stage II or III NEC were identified.…”
Section: Discussionmentioning
confidence: 87%
“…13 Few studies have evaluated the potential value of PTX as an adjuvant therapy in NS, but the current evidence is weakened by methodological issues in the included studied, and hence, the routine use of PTX in NS has not been recommended. A recent Cochrane review, 25 including 4 small RCTs and quasi-RCTs (227 neonates), has demonstrated that there is a significant reduction in all-cause mortality during hospital stay in neonates with sepsis who had PTX as an adjunct to antibiotics compared with neonates with sepsis who had placebo [typical relative risk: 0.40 (95% CI: 0.20-0.77); typical RD: 0.15 (95% CI: −0.26 to −0.05); number needed to treat: 7 (95% CI: [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]]. This finding is in contrast to the results of a RCT 19 and a small quasi-RCT, 22 and both demonstrated significant reduction in mortality in infants receiving PTX.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…aminophylline [14]. Over the past two decades, this non-steroidal immunomodulating agent has been used in a range of infectious, vascular and inflammatory conditions, including sepsis and multiorgan dysfunction syndrome in adults and infants, and in children with Kawasaki's disease [15][16][17]. It was shown in the experimental studies that pentoxifylline reduced foetal mortality and reversed LPS-induced foetal intra-uterine growth restriction and skeletal development retardation [18].…”
Section: Discussionmentioning
confidence: 99%